Mengurai Perbedaan Mukjizat Yesus Dalam Matius 8:5-13 Dan Lukas 7:1-10 Dalam Lensa Medis Dan Teologis - Adiatmo, Kumoro (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
This study aims to bridge the understanding of the medical conditions that may have occurred in the centurion's servants in Capernaum as recorded in the Gospels of Matthew (8:5-13) and Luke (7:1-10). This research shows that the differences in descriptions of the servant's condition between the two Gospels are natural and understandable in the context of the knowledge and observations of each author. The results of the analysis show that the descriptions of paralysis and great suffering in Matthew and near death in Luke are consistent with the symptoms of Amyotrophic Lateral Sclerosis (ALS). Thus, this study shows that variations in the Gospel narratives reflect diverse eyewitness perspectives and enrich our understanding of the complexity of the testimonies about Jesus' life and ministry. In this way, we can understand that these differences should not be considered as contradictions but rather as natural variations in eyewitness reports based on the different viewpoints and emphases of each author.